In silico analysis of PirA- and PirB-like toxin genes of Vibrio spp., present in Asia and Costa Rica - Guia, Arren Christian M De; Samson, Jaypee S; D Uy, Mary Rose (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Acute hepatopancreatic necrosis disease is an emerging infectious disease of Penaeusspecies. The causative agent is Vibrio species, which dispels binary toxin similar to pirA and pirB, which causes mortality in infected shrimp. The aim of this research was to investigate the evolutionary relationship of pirA and pirB homologous genes present in this Asia and Costa Rica in silico. Materials and methods: The sequences for in silicoanalysis were all retrieved from the Basic Local Alignment Search Tool Nucleotide (BLASTN) tool of the National Center for Biotechnology Center. For pirA, a total of 25 sequences submitted from different Asian countries and Costa Rica were retrieved for analysis. Meanwhile, for pirB, a total of 11 sequences submitted from five Asian countries were retrieved. Sequences were aligned using the CLUSTAL W alignment tool under Molecular Evolutionary Genetics Analysis (MEGA) 7 software. The evolutionary history was then estimated using the Unweighted Pair Group Method with Arithmetic mean (UPGMA) method, whereas the evolutionary distances were determined using the maximum composite likelihood model with 1,000 bootstrap replications. Results and Discussion: The results show that, among 27 DNA sequences analyzed for pirA gene, three groups were generated, while for pirB, 13 DNA sequences yielded only one group. The analysis revealed low genetic variation among isolates for both pirA and pirB genes. Conclusion: This result suggests that the low frequency of polymorphism and geographic location cannot be attributed to the differences in V. parahaemolyticusisolates in Asian countries relative to Costa Rican isolates in pirA and pirB genes. Adv. Vet. Anim. Res., 7(2): 320-323, June 2020